The Influence of Views, Economics, and Knowledge on Accounting Students' Interest in Sharia Investment (Empirical Study of Accounting Students at STIE 45 Mataram) - Nurlailah, Nurlailah; Rizqina, Intan; khairunnisah, Noni antika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Sharia Financial Institutions are based on the Al-Quran, Hadith and Ulama Ijtihad, in Indonesia sharia financial regulations are issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). This test aims to find out how much the dependent variable is influenced by individual independent variables.